The trend of bioremediation as an effective technology in soil decontamination - Bones, Ubiratan Alegransi; Flach, Kauane Andressa; da Rosa, Genesio Mario (Seven Editora, 2023)
This paper reviews the different techniques of bioremediation as a technology that uses living organisms, such as bacteria, fungi, and plants, to remove, degrade or transform contaminants present in soil, water, or air into less harmful substances. The research highlights the advantages of bioremediation for the mitigation of anthropogenic impacts on the environment, especially those caused by the use of herbicides and insecticides in agricultural practices. In addition, bioremediation can degrade a wide variety of contaminants, including hydrocarbons, heavy metals, pesticides, and toxic organic compounds, which can accumulate in the medium or be leached to contaminate water sources. In this context, it is emphasized that bioremediation can be applied directly to the contaminated site, reducing the need for the removal and transportation of large amounts of contaminated soil. This results in lower environmental impact and lower cost compared to other decontamination techniques. Another advantage of bioremediation is the integration of degraded contaminants into biogeochemical cycles, which contributes to the recovery of soil fertility and water quality. The technique also preserves biodiversity and ecosystem services, which can be affected by other decontamination techniques that alter the physical and chemical characteristics of the environment. However, there are also challenges and limitations of bioremediation, such as the possibility of partial degradation of the target compound and the formation of a more toxic or persistent by-product. This can occur due to the dependence on favorable environmental conditions, such as nutrients, oxygen, pH, composition, concentration, and bioavailability of contaminants, as well as the physical and chemical characteristics of soil and water. In addition, bioremediation is a promising tool for promoting the health and quality of life of populations affected by environmental contamination, but it requires an in-depth knowledge of the processes involved and a careful assessment of the risks and benefits.DOI:https://doi.org/10.56238/alookdevelopv1-145